PERCEIVED EASE AND SECURITY OF USING QRIS TOWARDS CASHLESS SOCIETY - Gideon Setyo Budiwitjacksono; Ahmad Septa (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Purpose: The purpose of the research journal is to investigate the perceptions of accounting students at UPN "Veteran" East Java regarding the implementation of a cashless society. Specifically, the study aims to explore the variables of Perception of Ease of Use of QRIS (Quick Response Code Indonesian Standard) and Perception of Security of QRIS. The researchers want to understand how these perceptions influence the adoption of a cashless society among accounting students. Design/methodology/approach: The research study employed a quantitative methodology and was placed during the academic year 2019-2020. The participants in the research were accounting students at UPN "Veteran" East Java. The researchers gathered data from these students and applied the SPSS Ver.26 software for analysis. To explore the connections between the variables of Perception Ease of Using QRIS, Perception of Security QRIS, and adoption a cashless society using multiple linear regression analysis. Findings: The study's results demonstrate that the adoption of a cashless society among accounting students at UPN "Veteran" East Java is affected by the perceived easeof using QRIS. That indicates a higher likelihood of embracing a cashless society observed when students perceive QRIS as user-friendly. Furthermore, the research reveals that the perception of QRIS security also play a role in influencing the adoption of a cashless society among accounting students. This suggests that a stronger inclination to embrace a cashless society is associated with perceiving QRIS as a secure payment method. Practical implications: The author recommends the government of Bank Indonesia and banking companies in conducting performance evaluations on the importance of QRIS-based payments accompanied by increased promotion and efficiency. Originality/value: This research is original and adds new value to the Cashless Society in Indonesia which is influenced by perceptions of convenience and perceptions of security